Bandwidth and Gain Enhancement of Wideband Slotted Patch Antennas Using Proximity-Coupled Feeding for Ku-Band Applications - Syach, Muhammad Danny Naufal; Wahdiyat, Aditya Inzani; Apriono, Catur (International Seminar on Intelligent Technology and its Applications, 2025)
This study presents the development and evaluation of a wideband slotted patch microstrip antenna designed for Ku-band satellite communication, incorporating reactive loading and proximity-coupled feeding methods. The antenna achieved a simulated operational frequency range of 11.41-15.04 \text{GHz} , with a bandwidth of 3.63 GHz and a reflection coefficient of -11.94 dB at 13 GHz. Measurements of the fabricated prototype revealed an operational range of 8.8-11.84 \text{GHz} and a bandwidth of 3.04 GHz, which were slightly narrower than simulated results due to fabrication tolerances and air gaps between substrate layers. The measured gain at the center frequency of 13 GHz reached 4.86 dB, demonstrating close agreement with simulated values and confirming the antenna's effectiveness for practical applications. Although minor deviations were observed, the proposed design proves to be a reliable and adaptable solution for wideband communication, particularly in fixed satellite services and Earth exploration. Future refinements in fabrication and assembly processes are expected to further enhance performance consistency and alignment between simulations and measurements.